IMPROVEMENT OF THE SUPPORTING STRUCTURE OF PLATFORM CAR FOR HIGHER EFFICIENCY OF CONTAINER TRANSPORTATIONS - Lovska, A. O. (Science and Transport Progress, 2017)
Purpose. The article is aimed to improve supporting structures of the platform car to increase the efficiency of container transportations. Methodology. In order to achieve the objective, the strength investigations of the universal platform car of the model 13-401 were conducted, strength reserves of the supporting elements were defined, and more optimal profiles of basic longitudinal beams of the frame in terms of the minimum material capacity were proposed. Decision correctness was confirmed by the strength calculation of the platform car supporting structure at basic loading operational modes and fatigue taking into account the research database of 107 cycles. It has been proposed to equip a platform car with swing fitting stops for fastening containers on the frame, which allows transportation of 20ft and 40ft containers. In order to improve container transportation efficiency along international transport corridors running through Ukraine, a platform car of articulated type has been designed on the base of the improved platform car structure. The mathematical simulation of dynamic loads of the platform car with containers (two 1CC containers) at operational loading modes has been carried out, the maximum accelerations influencing the support structure have been defined, and their multiple values have been considered in computer simulation of the strength of the platform car of articulated type. Findings. The support structure of the platform car of articulated type on the basis of the standard platform car has been developed. Refined values of dynamic loads influencing supporting structure the platform car of articulated type with containers at operational loading modes have been obtained; the maximum equivalent stresses in the platform car support structure have been defined. Originality and practical value. A mathematical model of displacements for a platform car of articulated type with containers at operational loading modes of supporting structure has been proposed. The strength model of the supporting structure for the platform car of articulated type based on the standard platform car has been developed. Results of the research can be used in designing of platform cars of articulated type to provide their strength at mixed transportations.